Nursing assistance in orthopedics and traumatology to indigenous patients: experience report (Research, Society and Development, 2022)
Aim: To report the experience of a nursing resident in the multiprofessional residency program in orthopedics and traumatology in indigenous patient care. Methodology: This is a descriptive study, of the experience report type. The environment of this experience report was the Municipal Hospital of Santarém. The mode of recording information in this report was done in a field diary of activities, with the construction and organization of memories of experiences that marked the resident's time in the sector of orthopedics and traumatology clinics. Results: It was evident during the practice that one of the difficulties encountered by the nursing resident was how to approach the patient and have a conversation to promote health education. Nurses must be creative and have the ability to use their skills to identify signs that harm the patient's life in order to implement measures to solve them. The interpretation of non-verbal language, expressed by the patient through his face as in moments when he presented pain, was essential to identify and seek a resolution. Final Considerations: The nursing care provided to the indigenous patient in the orthopedics and traumatology scenario was permeated by actions grounded on transculturality, as a key tool to achieve its objective. The residency is a space for anthropological discussions and how to do nursing in the face of the various cultural opportunities that we can find.